2020
DOI: 10.5194/mr-1-13-2020
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the residual line width under frequency-switched Lee–Goldburg decoupling in MAS solid-state NMR

Abstract: Abstract. Homonuclear decoupling sequences in solid-state nuclear magnetic resonance (NMR) under magic-angle spinning (MAS) show experimentally significantly larger residual line width than expected from Floquet theory to second order. We present an in-depth theoretical and experimental analysis of the origin of the residual line width under decoupling based on frequency-switched Lee–Goldburg (FSLG) sequences. We analyze the effect of experimental pulse-shape errors (e.g., pulse transients and B1-field inhomog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Typically, in fully protonated solids the resolution of the 1 H spectra obtained with PMLG decoupling at slow-moderate MAS frequencies or only ∼60 kHz MAS are comparable (Figure E,G) . Ernst and co-workers have recently demonstrated that the residual line width in PMLG decoupled 1 H spectrum at slow MAS arises primarily from two sources: (i) third-order autoterm for the homonuclear couplings and (ii) the deleterious effects of RF inhomogeneity . Note that the application of these decoupling sequences results in scaling of the isotropic chemical shift Hamiltonian.…”
Section: Decoupling Under Masmentioning
confidence: 95%
See 1 more Smart Citation
“…Typically, in fully protonated solids the resolution of the 1 H spectra obtained with PMLG decoupling at slow-moderate MAS frequencies or only ∼60 kHz MAS are comparable (Figure E,G) . Ernst and co-workers have recently demonstrated that the residual line width in PMLG decoupled 1 H spectrum at slow MAS arises primarily from two sources: (i) third-order autoterm for the homonuclear couplings and (ii) the deleterious effects of RF inhomogeneity . Note that the application of these decoupling sequences results in scaling of the isotropic chemical shift Hamiltonian.…”
Section: Decoupling Under Masmentioning
confidence: 95%
“…264 Ernst and coworkers have recently demonstrated that the residual line width in PMLG decoupled 1 H spectrum at slow MAS arises primarily from two sources: (i) third-order autoterm for the homonuclear couplings and (ii) the deleterious effects of RF inhomogeneity. 271 Note that the application of these decoupling sequences results in scaling of the isotropic chemical shift Hamiltonian. In the static case, the scaling factor is cos(θ m ) = 0.577.…”
Section: Homonuclear Decouplingmentioning
confidence: 99%
“…Then the reciprocal space of eq can be given via The FIDs will then be distributed in this k -space as shown schematically in Figure c, with angles varying from φ min for the fastest MAS rate to φ max for the slowest MAS rate. The angle φ is given by the ratio between the prefactor of the error terms (including residual couplings and shifts, due to imperfect averaging of dipolar couplings and chemical shift anisotropies that are responsible for the broadening in the spectra) , and the pure isotropic terms (isotropic chemical shifts). For a static sample φ st = 45° since ∑ m F m (ω MAS ) = 1.…”
Section: Methodsmentioning
confidence: 99%
“…The CRAMPS technique improved proton resolution at slower MAS but has been recently demonstrated to also limit the achievable resolution. 36,381 The CRAMPS approach was demonstrated to improve resolution in protein compared to only MAS spectra at slower MAS frequencies. 382 However, the method never really became popular, mainly due to limited proton resolution, RF heating, signal loss due to windowed acquisition, and multiparameter optimization for optimum decoupling performance.…”
Section: Applications To Proteinsmentioning
confidence: 99%